2016
DOI: 10.3389/fphys.2016.00246
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity before Sports Competition: A Systematic Review

Abstract: Sexual activity before competition has been considered as a possible cause for reduced performance since ancient Greece and Rome. Recently, the hypothesis that optimal sport performance could be influenced by a variety of factors including sexual activity before competition has been investigated. However, few scientific data are available, with the exception of anecdotal reports of individual experiences. The present systematic review focused on the current scientific evidence on the effects of sexual activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…No negative effect was found in the test results. In a recent systematic review about this topic, it has been concluded that data does not support the negative effects of sex before a competition (31), but in this review some important data from Vouyoukas, Pupiš et al, and Sztajzel et al studies about the negative effects of sex on athletic performance were neglected or not considered properly.…”
Section: Discussionmentioning
confidence: 97%
“…No negative effect was found in the test results. In a recent systematic review about this topic, it has been concluded that data does not support the negative effects of sex before a competition (31), but in this review some important data from Vouyoukas, Pupiš et al, and Sztajzel et al studies about the negative effects of sex on athletic performance were neglected or not considered properly.…”
Section: Discussionmentioning
confidence: 97%
“…24 Inter-rater reliability for individual component ratings will be determined by calculating the percentage of agreement and the Cohen's Kappa coefficient. 25 The remaining articles will be read in full and evaluated to determine their eligibility based on the inclusion and exclusion criteria. Finally, eligible articles will be included in the systematic review.…”
Section: Review Processmentioning
confidence: 99%
“…The screening process will be performed for both reviewers using Rayyan Software [37]. Inter-rater reliability for individual component ratings will be determined by calculating the percentage of agreement and Cohen's Kappa coefficient [38]. The remaining articles will be read in full and evaluated to determine their eligibility based on the inclusion and exclusion criteria.…”
Section: Review Processmentioning
confidence: 99%